2004
DOI: 10.1021/bi048775y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human 5-Lipoxygenase Activity by Membrane Lipids

Abstract: Mammalian 5-lipoxygenase (5-LO) catalyzes the conversion of arachidonic acid (AA) to leukotrienes, potent inflammatory mediators. 5-LO is activated by a Ca(2+)-mediated translocation to membranes, and demonstrates the characteristic features of interfacially activated enzymes, yet the mechanism of membrane binding of 5-LO is not well understood. In an attempt to understand the mechanism of lipid-mediated activation of 5-LO, we have studied the effects of a large set of lipids on human recombinant 5-LO activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 76 publications
6
55
0
Order By: Relevance
“…51,52 Furthermore, here we demonstrate that upon LOX-1 binding, AEA-containing liposomes undergo a partial dehydration of the membrane surface, as documented by the spectral shift of the carbonyl stretching band in FTIR analysis. This finding is in line with previous data on the interaction of human 5-LOX with synthetic vesicles 29 and provides further insights into the role of the surface properties of a lipid bilayer on membrane-interacting enzymes, like phospholipases, that undergo interfacial activation by the surrounding lipids. 48 The present data also suggest that HO-AEAs can be generated by LOX-1-dependent oxygenation of membraneembedded AEA and could diffuse laterally within the lipid bilayer to inhibit FAAH, 39 and/or activate NAPE-PLD, 22 thus sustaining a hyper-tone of AEA and subsequently an enhancement of its signaling.…”
Section: ■ Concluding Remarkssupporting
confidence: 91%
See 1 more Smart Citation
“…51,52 Furthermore, here we demonstrate that upon LOX-1 binding, AEA-containing liposomes undergo a partial dehydration of the membrane surface, as documented by the spectral shift of the carbonyl stretching band in FTIR analysis. This finding is in line with previous data on the interaction of human 5-LOX with synthetic vesicles 29 and provides further insights into the role of the surface properties of a lipid bilayer on membrane-interacting enzymes, like phospholipases, that undergo interfacial activation by the surrounding lipids. 48 The present data also suggest that HO-AEAs can be generated by LOX-1-dependent oxygenation of membraneembedded AEA and could diffuse laterally within the lipid bilayer to inhibit FAAH, 39 and/or activate NAPE-PLD, 22 thus sustaining a hyper-tone of AEA and subsequently an enhancement of its signaling.…”
Section: ■ Concluding Remarkssupporting
confidence: 91%
“…41 Previous data have indicated that the interaction of LOXs with model membranes can induce an overall stabilization of both the protein and the membrane. 28,29 Here, to dissect the effects of LOX-1 protein matrix from its enzyme activity on membrane properties, we used DPPC liposomes devoid of LOX-1 substrates, as well as AEA-containing LUVs incubated with the inactive apo-form of the enzyme. We found that in both cases, an enzyme concentration range of 0.1−1.0 μM did not affect the T m values of the membrane bilayer (data not shown).…”
mentioning
confidence: 99%
“…8 (728), and it has been suggested that a PC selectivity of the 5-LO could account for 5-LO targeting to the nuclear membrane (481). Membrane binding per se may, however, not confer 5-LO activity, and although Ca 2ϩ is required for 5-LO activity, 5-LO binds to, e.g., cationic phospholipids in the absence of Ca 2ϩ (761). The 5-LO is subject to phosphorylation by the MAPKs ERK1/2 and p38 MAPK (598,1087,1089), as well as by tyrosine kinases (540).…”
Section: A Arachidonic Acid Metabolitesmentioning
confidence: 99%
“…Ca 2ϩ has been shown to increase the affinity of 5-LO toward AA (24), to facilitate membrane association and binding to PC vesicles (21, 25), and appears to reduce the requirement of 5-LO for activating lipid hydroperoxides (26). For stimulation by phospholipids, apparently only the zwitterionic PC and a non-physiological cationic phospholipid (but not phosphatidylserine, phosphatidylethanolamine, phosphatidylinositol, or diacylglycerol (DAG)) stimulate 5-LO reactions (27,28). It has been proposed that 5-LO catalysis occurs at an interface between lipid and water, and the ratio of AA to phospholipid seems important for its activity (29).…”
Section: -Lipoxygenase (5-lo) Catalysis Is Positively Regulated By Camentioning
confidence: 99%